PROSES DAN MUTU KOPI BERAS DI TINGKAT RANTAI PASOK DARI DESA BENUANG GALING KECAMATAN SEBERANG MUSI KABUPATEN KEPAHIANG PROVINSI BENGKULU - Uker, Damres; Zuki, Meizul; Marniza, Marniza (BPFP Faperta UNIB, 2024)
Coffee is an agricultural commodity that is used as a source of livelihood for the people in Benuang Galing Village, Seberang Musi Districts, Kepahiang Regency. The supply chain of coffee bean is used to determine the activities of the relationships involved in distributing goods. The aim of this research is to identify the processes provided in each supply chain distribution flow and determine the quality at each level of the coffee supply chain on Benuang Galing Village. This research is a type of survey research with the snowball sampling method. A sample size of 25 respondents was obtained after no more new information was obtained from respondents regarding process data and other required data. The quality of coffee bean is determined using the method of the National Standards Agency. The research result shows the processes carried out at each level of the supply chain lead to an increase in the quality of coffee bean. Supply chain pattern I, the quality of coffee bean at collecting traders is included in grade 6 and for wholesalers the quality of coffee bean is included in grade 5, while in supply chain pattern II the quality of coffeen bean at wholesalers is included in grade 5.